Colour Reaction of Dibromo-p-chloro-chlorophosphonazo with Magnesium(II) and Analytical Application - Wang, Qing-Shuang; Zhai, Qing-Zhou (Asian Journal of Chemistry, 2013)
Using a complex colour reaction of DBC-chlorophosphonazo with magnesium(II), a spectrophotometric method for the determination of magnesium(II) has been developed. The apparent molar absorptivity of method is e620 nm = 2.03 × 104 L·mol-1·cm-1. Beer's law is followed over the range of 0-1.2 μg/mL for magnesium(II). Its regression equation is: A = 0.1604C (C:μg/mL) + 0.0079, with a correlation coefficient of r = 0.9993. The method has been satisfactorily applied to the determination of magnesium(II) in tobacco samples.